2022
DOI: 10.1155/2022/2019869
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound of Fetal Cardiac Function Changes in Pregnancy-Induced Hypertension Syndrome

Abstract: Pregnancy-induced hypertension syndrome (PIH) is a common pregnancy syndrome that could cause varying degrees of maternal and fetal organic damage and even endanger their lives. This study aimed to investigate ultrasound of fetal cardiac function changes in PIH. Totally 40 cases of gestational hypertension admitted to Cangzhou Central Hospital between October 2018 and September 2019 were enrolled in the hypertension group, and 40 women with healthy pregnancies during the same period were assigned to the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%